HUBUNGAN MINAT MELANJUTKAN STUDI KE PERGURUAN TINGGI DENGAN PRESTASI BELAJAR SISWA JURUSAN TEKNIK MESIN SMK NEGERI 1 BUKITTINGGI - Vickram Reski Andri; Dori Yuvenda; Rifelino Rifelino; Randi Purnama Putra (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Student academic achievement in vocational high schools (SMKs) is influenced by various internal factors, one of which is the interest in pursuing higher education. A preliminary survey of Mechanical Engineering students at SMK Negeri 1 Bukittinggi indicated differences in academic achievement between students intending to continue their studies and those planning to enter the workforce directly. This study aimed to examine the relationship between students' interest in pursuing higher education and their academic achievement. A quantitative associative approach with an ex post facto design was employed. The population consisted of Mechanical Engineering students in the 2025/2026 academic year, with a sample of 59 respondents selected using Proportional Stratified Random Sampling. Data were collected through a questionnaire to measure students' interest in pursuing higher education and report card records to measure academic achievement. Data were analyzed using the Pearson Product-Moment Correlation test. The findings revealed a positive and statistically significant relationship between interest in pursuing higher education and academic achievement (r = 0.426, p = 0.001 < 0.05). The coefficient of determination (R² = 0.182) indicated that interest in pursuing higher education accounted for 18.2% of the variance in students' academic achievement. These findings suggest that a stronger interest in pursuing higher education is associated with better academic achievement among vocational high school students. ABSTRAKPrestasi belajar siswa Sekolah Menengah Kejuruan (SMK) dipengaruhi oleh berbagai faktor internal, salah satunya minat melanjutkan studi ke perguruan tinggi. Survei awal pada siswa Jurusan Teknik Mesin SMK Negeri 1 Bukittinggi menunjukkan adanya perbedaan rata-rata prestasi belajar antara siswa yang berminat melanjutkan studi dan yang memilih langsung bekerja. Penelitian ini bertujuan untuk mengetahui hubungan antara minat melanjutkan studi ke perguruan tinggi dengan prestasi belajar siswa Jurusan Teknik Mesin SMK Negeri 1 Bukittinggi. Penelitian menggunakan metode kuantitatif asosiatif dengan desain ex post facto. Populasi penelitian adalah siswa Jurusan Teknik Mesin tahun ajaran 2025/2026 dengan sampel sebanyak 59 responden yang dipilih menggunakan teknik Proportional Stratified Random Sampling. Data dikumpulkan melalui angket untuk mengukur minat melanjutkan studi dan dokumentasi nilai rapor untuk mengukur prestasi belajar. Analisis data menggunakan korelasi Pearson Product Moment. Hasil penelitian menunjukkan terdapat hubungan positif dan signifikan antara minat melanjutkan studi dengan prestasi belajar (r = 0,426; p = 0,001 < 0,05). Koefisien determinasi (R²) sebesar 0,182 menunjukkan bahwa minat melanjutkan studi memberikan kontribusi sebesar 18,2% terhadap prestasi belajar siswa. Dengan demikian, semakin tinggi minat siswa untuk melanjutkan studi ke perguruan tinggi, semakin baik prestasi belajar yang dicapai.